The Position of Consideration in Nepal: a Study of Theories, Cases, and Laws - Sapkota, Laxmi (Kathmandu School of Law Review, 2020)
Lawful consideration is one of the essential elements of a valid contract. However, The National Civil Code, 2017 A.D. (2074 B.S.) has not included a definition of consideration, and it has not stated the necessity of consideration in Nepal in a particular section. Nevertheless, it seems that the Code has realized the importance of lawful consideration in the provisions of contracts of rent, wage and hire purchase. The Code has also stated unjust enrichment, under which one party should not enrich himself or herself at the cost of others or other’s property. Conversely, the now-repealed Contract Act, 2000, in its section 2(d), had defined consideration and stated that consideration must be lawful in section 13(k). In the cases decided by the Supreme Court of Nepal (Bhagwan Lal Shah v. Harka Lal Giri and Chitra Bahadur Karki; Proprietor of Manakamana Construction and Concerns Pvt. Ltd v. Maniram Aggrawal, Proprietor of Aggrawal Industries Pvt. Ltd.), the Supreme Court has issued the precedent stating the importance of consideration in Nepal in regard to Contract Act, 2000 which has now been repealed and replaced by The National Civil Code 2017. Additionally, different theories of the contract like bargain theory, realistic interpretation, theory of reciprocity, ‘nundum pactum’ theory and ‘no consideration no contract’ theory also emphasize the importance of consideration in Contract. Finally, this research paper has proven that consideration is essential in Nepal, thereby stating the theories of consideration, the legislative provisions, and the cases. Furthermore, the researcher came to the conclusion that the lawful consideration is essential in Nepal and it should be dealt with like oxygen to humans and whether written or not, must be implicitly understood. The word ‘consideration’ not explicitly being mentioned in law should not create confusion that a contract can happen without lawful consideration.